Solicitous use of injection remdesivir, tablet baricitinib, and plasma therapy for severe COVID-19 patient associated with Stage 4 sarcoidosis and type 2 diabetes mellitus: A case report - Megha Bajaj,; Ashok K Saxena,; Suman Choudhary,; Sapna Jain, (Indian Journal of Case Reports, 2021)
COVID-19 infection caused by single-stranded RNA virus was declared as a global pandemic by the WHO. Various concomitant diseases including diabetes, hypertension, and sarcoidosis increase mortality and morbidity in patients with COVID-19 infection. In this present case report, we effectively treated a severe COVID-19 patient with Stage 4 pulmonary sarcoidosis and type 2 diabetes mellitus who required intensive care unit using a multimodal approach including injection remdesivir, baricitinib, plasma therapy, graded oxygen therapy, and other supportive care.